De-Medicalizing Misery II
XXV, 283 p.
Keywords: This book extends the critical scope of the previous volume, De-Medicalizing Misery, into a wider social and political context, developing the critique of the psychiatrization of Western society. It explores the contemporary mental health landscape and poses possible alternative solutions to the continuing issues of emotional distress.